The Personalised Acne Care Pathway-Recommendations to guide longitudinal management from the Personalising Acne: Consensus of ExpertsCapsule Summary - Jerry Tan, MD; Andrew Alexis, MD, MPH; Hilary Baldwin, MD; Stefan Beissert, MD; Vincenzo Bettoli, MD; James Del Rosso, DO; Brigitte Dréno, MD, PhD; Linda Stein Gold, MD; Julie Harper, MD; Charles Lynde, MD; Diane Thiboutot, MD; Jonathan Weiss, MD; et al. (Elsevier, 2021)
Background: Acne is a chronic disease with a varying presentation that requires long-term management. Despite this, the clinical guidelines for acne offer limited guidance to facilitate personalized or longitudinal management of patients. Objectives: To generate recommendations to support comprehensive, personalized, long-term patient management that address all presentations of acne and its current and potential future burden. Methods: The Personalising Acne: Consensus of Experts panel consisted of 13 dermatologists who used a modified Delphi approach to reach consensus on statements related to longitudinal acne management. The consensus was defined as ≥75% voting "agree" or "strongly agree." All voting was electronic and blinded. Results: Key management domains, consisting of distinct considerations, points to discuss with patients, and "pivot points" were identified and incorporated into the Personalised Acne Care Pathway. Long-term treatment goals and expectations and risk of (or fears about) sequelae are highlighted as particularly important to discuss frequently with patients. Limitations: Recommendations are based on expert opinion, which could potentially differ from patients' perspectives. Regional variations in health care systems may not have been captured. Conclusions: The Personalised Acne Care Pathway provides practical recommendations to facilitate the longitudinal management of acne, which can be used by health care professionals to optimize and personalize care throughout the patient journey.